TRADISI YASINAN PADA MALAM JUMAT (STUDI LIVING QUR’AN DI PONDOK PESANTREN AS’ADIYAH SENGKANG) - Tahir, Muhyiddin; Latif, Abdul; Baharuddin, Muhammad (Ma'had Aly As'adiyah Sengkang, 2024)
This article elaborates on the concept of the living Qur’an at the As'adiyah Islamic Boarding School in Sengkang, with a focus on analyzing the interaction between the As'adiyah community and the Qur'an in the tradition of Yasinan on Friday nights. This study is significant due to its connection to the history of the tradition and perspectives on its practice. Through qualitative research, the author aims to delve deeper into this tradition. The objectives of this study are: First, to understand the practice of the Yasinan tradition at the As'adiyah Islamic Boarding School in Sengkang. Second, to explore the purpose of the Yasinan tradition at the As'adiyah Islamic Boarding School in Sengkang. Third, to uncover the wisdom gained from the Yasinan tradition at the As'adiyah Islamic Boarding School in Sengkang.The method used in this study is qualitative descriptive research, where the researcher presents data and facts scientifically without influencing the subjects or objects of the study in any way. The results of the study indicate that the practice of the Yasinan tradition on Friday nights at the As'adiyah Islamic Boarding School in Sengkang has not been precisely determined in terms of its origin. Furthermore, the Yasinan practice is led by one person who recites Surah Al-Fatiha, followed by the recitation of Surah Ya-Sin.The goals and wisdom derived from the Yasinan tradition, when viewed from the perspective of the Qur'an, show no contradiction or prohibition. In addition to the focus on reward, there are personal and social benefits, including the fostering of unity and solidarity, which can enhance a strong sense of social responsibility.Keywords : (Living Qur’an, Yasinan, As’adiyah)